Peran Sekretaris Desa Dalam Pelayanan Administrasi Umum Di Desa Lumpoknyo - Ade Putra Ode Amane; Abdul Haq; Haminun Dg. Matorang; Susanti Susanti (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
This paper aims to determine the role of the Village Secretary in Public Administration Services in Lumpoknyo Village, Luwuk District, Banggai Regency. The research method uses primary data and secondary data. Methods of data collection using observation techniques, questionnaires, literature studies and documentation. The technique used is statistical analysis using statistical formulas (percentages) that are used to describe the results of the study. The calculation of the data is given a score based on the type of data collected, namely qualitative data which is then converted into quantitative. After selecting the data, then giving a score weight for each alternative answer in scoring using a Likert Scale. Then determine the variables measured based on the indicators studied. Based on the results of distributing questionnaires to respondents that the Role of the Village Secretary in General Administrative Services in Lumpoknyo Village, Luwuk District, Banggai Regency, based on the rating scale, was classified as good with a Secretary Role score of 76.78% and General Administration Services 76.13%.